2020
DOI: 10.1007/s10886-020-01163-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Grass - Endophyte Chemotypes on a Tri-Trophic Cascade

Abstract: Systemic grass-endophytes of the genus Epichloë symbiotically infect the above-ground plant parts of many grass species, where they produce alkaloids in a grass-and endophyte-specific manner that are toxic or deterrent to herbivores. An increasing number of studies show cascading negative effects of endophyte-derived alkaloids that extend to higher trophic levels, harming beneficial insects, including those that control aphid populations. Lacewings are one of the major biological aphid controls, and are especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Epichloë endophytes grow in the intercellular space of the leaves, stems, and reproductive tissue of several cool-season grasses and are typically absent in the roots [ 53 , 54 ], indicating that their effect on shaping fungal community structure is limited to aboveground plant parts. This is in agreement with our previous study, where Epichloë symbiosis in tall fescue ( Schedonorus phoenix ) impacted only the endophytic fungal community in leaves, not the bacterial community [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epichloë endophytes grow in the intercellular space of the leaves, stems, and reproductive tissue of several cool-season grasses and are typically absent in the roots [ 53 , 54 ], indicating that their effect on shaping fungal community structure is limited to aboveground plant parts. This is in agreement with our previous study, where Epichloë symbiosis in tall fescue ( Schedonorus phoenix ) impacted only the endophytic fungal community in leaves, not the bacterial community [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our previous study, ergot alkaloid concentrations varied considerably among E+ plants in the present study. Similarly, many other studies with other grass species have revealed that the quantities of Epichloë alkaloids vary among geographic origin and genetic plant-fungus combinations and can be plastic during the growing season depending on environmental conditions (Siegel et al, 1990;Thom et al, 2014;Helander et al, 2016;König et al, 2018;Fuchs et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Another reason may be the age of the plants or cultivar specific performance. Some studies have indicated that the beneficial effect of endophytes is frequently missing during the first year of plant establishment or highly strain specific (Fuchs et al, 2017b(Fuchs et al, , 2020König et al, 2018).…”
Section: Discussionmentioning
confidence: 99%